Steps for conducting a valid hydraulic fracturing laboratory test - Sarmadivaleh, Mohammad; Joodi, Bahman; Nabipour, Amin; Rasouli, Vamegh (Australian Petroleum Production and Exploration Association Limited, 2013)
Several parameters are involved in a hydraulic-fracturing operation, which is a technique used mainly in tight formations to enhance productivity. Formation properties, state of stresses in the field, injecting fluid characteristics, and pumping rate are among several parameters that can influence the process. Numerical analysis is conventionally run to simulate the hydraulic-fracturing process. Before operating the expensive fracturing job in the field, however, it would be useful to understand the effect of various parameters by conducting physical experiments in the lab. Laboratory experiments are also valuable for validating the numerical simulations. Applying the scaling laws, which are to correspond to the field operation with the test performed in the lab, are necessary to draw valid conclusions from the experiments. Dimensionless parameters are introduced through the scaling laws that are used to scale-down different parameters including the hole size, pump rate and fluid viscosity to that of the lab scale. Sample preparation and following a consistent and correct test procedure in the lab, however, are two other important factors that play a substantial role in obtaining valid results. The focus of this peer-reviewed paper is to address the latter aspect; however, a review of different scaling laws proposed and used will be given. The results presented in this study are the lab tests conducted using a true triaxial stress cell (TTSC), which allows simulation of hydraulic-fracturing under true field stress conditions where three independent stresses are applied to a cubic rock sample.